Can Improving Soft Skills Increasing Women’s Employment in STEM? - Damayanti, Rolly Aruna; Yuliati, Yayuk; Kholifah, Siti (Devotion : Journal of Research and Community Service, 2023)
Employment in the Science, Technology, Engineering, and Mathematics (STEM) sector is associated with men’s occupation. STEM is perceived to be more suitable for men mirroring the long-held gender stereotyping of occupations. With the growth in automation and digitalization, women have more opportunities to find jobs in the STEM sector. However, to avail of these opportunities, women need support to adapt to the changes in the job market by developing soft skills that can complement their technical competencies. The present research aims to investigate how soft skills training can help female STEM graduates in the transition from school to work. The study uses a qualitative approach with a descriptive phenomenological method. Data was collected through interviews and a literature review. The findings of this research demonstrate that soft skills training improved self-confidence and helped female graduates to prepare better for jobs in the STEM sector. The study argues additional program and support such as structured soft skills training needed to better prepare female students compete in STEM’s employment. By doing so, the number of women who wish to study and pursue a career in the STEM sector can be increased. Soft skills training can improve work readiness and create a more level playing field for women in the STEM sector.